HYPERTENSION RISK FACTOR ANALYSIS IN COMMUNITY: A CASE STUDY IN THE COMMUNITY OF BATURETNO VILLAGE, DAMPIT DISTRICT, MALANG REGENCY - Naura Anindya Candini; Yunita Lestari Indrianto; Deden Ahmad Iqromi; Azzura Jasmine Simanulang; Gusti Rajendra Yoga Pratama; Devita Rahmani Ratri; Shofi Nur Rahmah (Journal of Community Health and Preventive Medicine, 2023)
Hypertension is one of the non-communicable diseases which has been identified as the main cause of premature death in the world. In 2020, the number of people with hypertension in Malang Regency reached 704,698 people, making Malang Regency the third-highest hypertension rate regency in Java. In Dampit District, the prevalence of hypertension was 3.31% with 1,019 residents were diagnosed with this disease. Better management of hypertension is needed, considering the high morbidity and mortality caused by the disease. This study aimed at determining the main gap in knowledge, attitude, and practice about hypertension; as well as investigating the effect of health promotion on knowledge about hypertension of the residents of Baturetno Village, Dampit District, Malang Regency. We employed a pre-experimental one-group pretest post-test design. The study was conducted on 11-18 January 2022, involving 50-82 samples who were selected through consecutive sampling. This study consisted of 2 stages. The first stage used the questionnaire to identify the gap in the knowledge, attitude, and practice about hypertension. The result was then analyzed using Chi-Square, then the main problem was selected using the Nominal Group Technique. In the second stage, we developed a health promotion to address issues selected in the first stage. Wilcoxon was used to analyze the impact of the promotion on respondents’ knowledge. We found that the main risk factor for hypertension in Baturetno Village was the low level of knowledge regarding the use of hypertension drugs. We found a significant increase in the level of knowledge after health promotion was delivered through roleplay and simulation.